2016
DOI: 10.1021/acs.est.6b03886
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Nitrification-Denitrification Caused by Suspended Sediment (SPS) in Rivers: Importance of SPS Size and Composition

Abstract: Suspended sediment (SPS) is ubiquitous in rivers, and SPS with different particle sizes and compositions may affect coupled nitrification-denitrification (CND) occurring on SPS significantly. However, there is no related research report. In this work, N isotope tracer technique was adopted to explore the CND in systems containing SPS (8 g L and 1 g L) collected from the Yellow River with various particle sizes, including <2, 2-20, 20-50, 50-100, and 100-200 μm. The results showed that the CND occurred on SPS a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…Recently, a series of 15 N isotopic tracer studies have suggested that the nitrification/denitrification rates in oxic water are significantly affected by the abundances of nitrifiers/denitrifiers on the suspended particles 44 47 . Although the current study did not make direct measurement of nitrification or denitrification rate, on the basis of results above, we assume that the abundances of nitrifiers/denitrifiers on SPM can also reflect (to some extent) nitrification/denitrification rates in the turbid water of Hangzhou Bay.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a series of 15 N isotopic tracer studies have suggested that the nitrification/denitrification rates in oxic water are significantly affected by the abundances of nitrifiers/denitrifiers on the suspended particles 44 47 . Although the current study did not make direct measurement of nitrification or denitrification rate, on the basis of results above, we assume that the abundances of nitrifiers/denitrifiers on SPM can also reflect (to some extent) nitrification/denitrification rates in the turbid water of Hangzhou Bay.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon, nutrients, and microbes are all impacted by the dynamic transport and retention of fine particles [ Hope et al ., ; Gottselig et al ., ; Xia et al ., ]. Therefore, particle dynamics must be considered when evaluating water column, benthic, and hyporheic biogeochemical processes.…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria, which preferentially attach to fine sediment [Walters et al, 2014], interact with this highly mobile fraction of POC thus enhancing heterotrophic metabolism [Cushing et al, 1993;Battin et al, 2003Battin et al, , 2016. Sediment size and composition, in particular the association of smaller sediment with higher organic carbon content, influences nitrogen cycling in streams [Xia et al, 2017]. Sorption to fine particles is known to occur for ammonium [Triska et al, 1994], and to an even greater extent for soluble reactive phosphorus, where 2-5 times more phosphorus sorbed to fine particulates is transported within riverine systems as compared to the dissolved load [Froelich, 1988].…”
Section: Introductionmentioning
confidence: 99%
“…Various sedimentology formulas have been proposed to quantify the sediment processes, with sediment particle size being a critical parameter in those formulas (Meyer-Peter and Müller, 1948;Einstein, 1950;Engelund and Hansen, 1967;Ackers and White, 1973;Van Rijn, 1984;Parker 1990;Garcia and Parker, 1991;Wu et al, 2000;An et al, 2021). Moreover, sediment particle size is a critical factor in riverine dynamics of heavy metal (Unda-Calvo et al, 2019;Zhang et al, 2020), nutrients (Xia et al, 2017;Glaser et al, 2020), microplastic (Corcoran et al, 2019;He et al, 2020), and fish habitats and benthic lives (Dalu et al, 2020;Rieck and Sullivian, 2020).…”
Section: Introductionmentioning
confidence: 99%